A validated surrogate analyte UPLC–MS/MS assay for quantitation of TUDCA, TCDCA, UDCA and CDCA in rat plasma: Application in a pharmacokinetic study of cultured bear bile powder. (7th April 2020) - Zan, Bin; Liu, Xinhua; Zhao, Yining; Shi, Rong; Sun, Xiaoshu; Wang, Tianming; Li, Yuanyuan; Liu, Shaoyong; Yang, Li; Ma, Yueming
Abstract: Bear bile is a valuable medicinal material used in traditional Chinese medicine for over 2000 years. However, developing a substitute has become necessary because of protection measures for this endangered species. The ingredients of in vitro cultured bear bile powder (CBBP) include tauroursodeoxycholic acid (TUDCA), taurochenodeoxycholic acid (TCDCA), ursodeoxycholic acid (UDCA) and chenodeoxycholic acid (CDCA, and it has pharmacological properties that are similar to those of natural bear bile powder (NBBP). In this study, the pharmacokinetic parameters of both CBBP and NBBP were measured in rats with a new surrogate analyte LC–MS method using stable isotopes as surrogate analytes (D4‐TUDCA, D4‐TCDCA, D4‐UDCA and D4‐CDCA) with response factors validated in authentic matrix (plasma) for simultaneously monitoring the authentic analytes (TUDCA, TCDCA, UDCA and CDCA). The method validation was satisfactory for the linear regression ( r, 0.9975–0.9994), precision (RSD intra‐day, 0.72–9.35%; inter‐day, 3.82–9.02%), accuracy (RE, −12.42–5.67%) and matrix effect (95.53–99.80%), along with analyte recovery (95.90–98.82%) and stability (89.48–101.81%) of surrogate analytes, and precision (RSD intra‐day, 1.06– 11.51%; inter‐day, 2.23– 11.38%), accuracy (RE, −7.40–10.76%) and stability (87.37–111.70%) of authentic analytes. We successfully applied this method to evaluate the pharmacokinetics of CBBP and NBBP in rats, which revealed the critical in vivo properties of both bear bile preparations.